Profitability of Hybrid Maize (Zea mays L.) Seed Production Under Contract Farming in Bangladesh: A Farm Level Study - Haque, MA; zaman, Monir uz; Rahman, MS; Alam, QM (Bangladesh Journal of Agricultural Research, 2012)
The study was conducted with three catagories of seed producers, namely BADC farms at Dattanagar, Jhenaidah and Tabunia, Pabna as public agency, LAL TEER Seed Company in Lalmonirhat district as private company and BRAC farm in Bogra district as NGO during Rabi season of 2007-08 to know the present status and profitability of hybrid maize seed production. A total of 60 hybrid maize seed contract growers and 120 maize (Non-seed) growers were selected randomly for the study. The cost of production was found higher for NGO (Tk. 66472/ha) than the public agency (64836/ha) and private company (Tk. 59352/ha). The yield of hybrid seed was highest under NGO (3780 kg/ha) than that of public agency and private company. Net return of hybrid seed production for contract growers was higher under public agency (Tk. 78204/ha) compared to private company (Tk. 39088/ha) and NGO (Tk. 33246/ha). Benefit cost ratio (BCR) was higher for the contract growers of public agency (2.21) Net return of hybrid maize seed production was 50% higher than that of non-seed production. High price of seed and lack of technical knowledge were major constraints of hybrid maize seed production in the study areas. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11237 Bangladesh J. Agril. Res. 37(2): 327-334, June 2012